The effects of polymer concentration, shear rate and temperature on the gelation time of aqueous Silica-Poly(ethylene-oxide) “Shake-gels” - Collini, Harry; Mohr, Markus; Luckham, Paul; Shan, Jiawen; Russell, Andrew (Journal of colloid and interface science, 2018)
[Display omitted] Aqueous mixtures of silica and Poly(ethylene-oxide) (PEO) are known as “Shake-gels” due to the formation of reversible gels when subject to an applied force, such as shaking. This shear-thickening effect can be observed using a rheometer, via distinct and abrupt increases in the viscosity of the material. Preliminary experiments qualitatively showed that the time elapsed before this occurs, termed the gelation time, varied depending on the conditions used. This paper reports on a systematic study into the effects of polymer concentration, shear rate and temperature on the gelation time, to quantify any relationships that exist between the variables and develop understanding of the gelation mechanism and kinetics. Different constant shear rates were applied to samples at various polymer concentrations and temperatures using a rheometer with concentric cylinder geometry. The gelation time varied significantly from several seconds to an hour or more and was exponentially accelerated by shear rate. A peak in gelation time occurred at medium polymer concentrations of 0.35–0.40% (25% silica) and at a temperature about 20 °C. Higher temperatures also exponentially accelerated the gelation time as kinetic effects dominated the thermodynamic and structural resistances to gel formation.